Genetic tests: what’s up in Europe? On the margin of European Commission’s Report and Recommendations on the ethical, legal and social implications of genetic testing. - Gainotti, Sabina; Spagnolo, Antonio G. (Medicina e Morale, 2004)
On 6 and 7 may 2004 a congress organised by the European Commission took place in Brussels, to stimulate the reflection over the ethical, social and legal implications of human genetic testing. The Authors report the conclusion of that two days congress dedicated to the analysis and discussion of 25 recommendations written by a multidisciplinary group, who was composed by politicians, academics, industry and patients representatives of many European countries. The quality of available genetic tests, the accuracy of their results, the conditions for accessing to genetic testing and therapies (mostly for people with genetic rare diseases), the appropriate use of samples and data, informed consent and the respect for privacy and confidentiality, genetic counselling before and after tests, the risks of new discriminations based on gender or race: these are only some of the problems discussed during the congress. The 25 recommendations of the European Commission are somehow different from other international documents and declarations, mostly for what concerns the "statute" assigned to genetic data ("genetic exceptionalism"); according to the Group who wrote the recommendations, genetic data aren't different from other medical data, and they shouldn't be treated in a different way. However, new knowledge and information arise from genetic tests, and this could complicate the relationship between patients, their physicians, and their families. As the use of genetic tests will increase, there will be a need for more clear and acceptable rules for all the involved parties: physicians, patients and families will have to solve practical problems, and they will have to conciliate all their different rights (e.g. the patient's right to know and not to know, to disclose and not to disclose to others the test results), and responsibilities (e.g. for physicians, the duty to keep professional secret, to protect privacy, but sometimes also the duty to warn third parties). Informed consent should help patients to understand all the implications of a test, from its possible impact on familiar and social life, to the storage and use of medical and clinical data for future researches. When the "object" being studied is not only an individual but a family or a group (e.g. in genetic screenings), a "group consent" will be needed, while population studies should result in a more public and democratic debate. Finally, there is a last important question: all these new possibilities, will they result in a more costly or costless public health? The possible future scenarios are many, but these depend not only from science. To ensure that the potential benefits of genetic testing overcome their risks, it will be necessary to create a responsible normative framework, both at the single States level, and at the European one.